2010
DOI: 10.1111/j.1749-6632.2009.05338.x
|View full text |Cite
|
Sign up to set email alerts
|

Work and its role in shaping the social gradient in health

Abstract: Adults with better jobs enjoy better health: job title was, in fact, the social gradient metric first used to study the relationship between social class and chronic disease etiology, a core finding now replicated in most developed countries. What has been less well proved is whether this correlation is causal, and if so, through what mechanisms. During the past decade, much research has been directed at these issues.Best evidence in2009 suggests that occupation does affect health. Most recent research on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
151
0
6

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 191 publications
(165 citation statements)
references
References 177 publications
(286 reference statements)
8
151
0
6
Order By: Relevance
“…Sie werden im Folgenden skizziert. Eine erste Erklärung hierfür liegt im Zusammenhang zwischen beruflicher Position und Bildung sowie Einkommen [12,23,24].…”
Section: Erklärung Gesundheitlicher Ungleichheit Bei Beschäftigenunclassified
See 1 more Smart Citation
“…Sie werden im Folgenden skizziert. Eine erste Erklärung hierfür liegt im Zusammenhang zwischen beruflicher Position und Bildung sowie Einkommen [12,23,24].…”
Section: Erklärung Gesundheitlicher Ungleichheit Bei Beschäftigenunclassified
“…So ist der Bildungserfolg in vielen Ländern von der sozialen und ökonomischen Situation der Herkunftsfamilie abhängig [26]. Dies kann dazu führen, dass junge Erwachsene mit niedrigen Bildungsabschlüssen schon beim Eintritt in das Berufsleben vorbelastet sind, da sie bereits während ihrer Kindheit und Jugend mit negativen gesundheitlichen Folgen von Armut und Benachteiligung konfrontiert waren [23]. Gesundheitliche Selektionseffekte können zudem im gesamten Ver- [11,30,31,33,36,[39][40][41].…”
Section: Erklärung Gesundheitlicher Ungleichheit Bei Beschäftigenunclassified
“…Os estudos têm fornecido evidências de que o trabalho e a ocupação contribuem para o gradiente da associação inversa entre inserção social e saúde. Hierarquia ocupacional, estressores psicossociais, condições de trabalho ou perda do emprego são alguns dos mecanismos por meio dos quais o trabalho pode contribuir com esse gradiente 14 . Em decorrência das mudanças socioeconômicas estruturais ocorridas no final do século passado, o impacto das formas de trabalho precárias ganhou relevância na investigação da relação trabalho e saúde.…”
Section: Introductionunclassified
“…The associations between employment status and the incidence and prevalence of chronic diseases and mortality have been previously discussed (Mackenbach et al, 2008;Clougherty et al, 2010). Minis et al (2010) reported that employed patients with neuromuscular diseases had better perceived health status than nonemployed patients.…”
Section: Introductionmentioning
confidence: 99%